Phosphaturic mesenchymal tumor and related wound problem - Xiao, Xian (Medicine (Baltimore), 2018)
INTRODUCTION: Phosphaturic mesenchymal tumor mixed connective tissue type (PMT/MCT) is the most common type (up to 90%) of phosphaturic mesenchymal tumor (PMT), a rare clinicopathologic entity. Besides overproduction of fibroblast growth factor 23 (FGF23), there is a big variation of immunohistochemical characteristic across types of PMT, which makes it difficult to obtain an early diagnosis of PMT/MCT. As a benign tumor, PMT/MCT usually happens in subcutaneous tissues and leads to nonhealing of wound. A complete excision of PMT/MCT facilitates wound healing. CONCLUSIONS: Review of the existing evidence indicates that early diagnosis of PMT/MCT is critically important when treating PMT/MCT wound. Hence standardization of early diagnosis for PMT/MCT is mandated.